2018
DOI: 10.21783/rei.v3i2.228
|View full text |Cite
|
Sign up to set email alerts
|

Cotas Da Reserva Ambiental: Uma Interpretação Da Análise Econômica Do Direito

Abstract: No Novo Código Florestal (Lei nº 12.651/2012), a obrigação dos proprietários rurais de manter uma área de vegetação nativa (ou Área de Reserva Legal – ARL) foi flexibilizada pela introdução das Cotas de Reserva Ambiental (CRA). Por meio da organização de um Mercado de compensação, as CRA permitem que proprietários rurais com déficit de ARL regularizem sua situação por meio da compra de CRA daqueles com superávit de ARL (limitado ao mesmo bioma). Através de revisão bibliográfica e pesquisa jurídica, analisamos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Scoton (2016) reports that for the ERQ to fulfill its preservation objective, it is necessary to guarantee that the income earned in its commercialization is actually destined to the maintenance and conservation of the compensable area. According to Porto and Santos (2017), the motivation or incentive for maximum effort within the scope of ERQ should be leveraged from the moment the instrument is fully operational, so that the activity of negotiations between CRA applicants According to Silva and Ranieri (2014), ERQ is able to promote environmental conservation by effectively maintaining remnants of native vegetation in rural areas with lower opportunity and implementation costs. Gasparinetti and Vilela (2018) reported that ERQ, in principle, does not have the long-term objective of reducing deforestation, but of maintaining the balance of deforested and compensated areas.…”
Section: Legal Framework and Environmental Legislationmentioning
confidence: 99%
“…Scoton (2016) reports that for the ERQ to fulfill its preservation objective, it is necessary to guarantee that the income earned in its commercialization is actually destined to the maintenance and conservation of the compensable area. According to Porto and Santos (2017), the motivation or incentive for maximum effort within the scope of ERQ should be leveraged from the moment the instrument is fully operational, so that the activity of negotiations between CRA applicants According to Silva and Ranieri (2014), ERQ is able to promote environmental conservation by effectively maintaining remnants of native vegetation in rural areas with lower opportunity and implementation costs. Gasparinetti and Vilela (2018) reported that ERQ, in principle, does not have the long-term objective of reducing deforestation, but of maintaining the balance of deforested and compensated areas.…”
Section: Legal Framework and Environmental Legislationmentioning
confidence: 99%